A micro-level study of the economic losses of traffic congestion delays in Srinagar city of Kashmir valley - Farzana Ahad; Huma Rashid; Shamim Ahmad Shah; Mohammad Shafi Bhat; Peer Jeelani (Discover Cities)
Abstract Traffic congestion is a common problem in developing countries, especially in major cities that cost huge sums of money and labour hours, and all signs point to it worsening in the future, endangering the quality of urban life. Evaluating the economic implications of urban traffic congestion is essential for improving productivity, maximizing infrastructure investments, and developing efficient transportation regulations. The goal of the current study is to estimate the costs associated with traffic congestion on the main routes that connect Srinagar City, the only metropolis in the Kashmir Valley of India, with other districts. This study employed an on-site survey methodology to gather data from habitual road users by distributing questionnaires, conducting volume count surveys, and monitoring travel time, delay time, and vehicle speed throughout the day. The results indicate that an estimated 69.87 million INR (0.8514 million USD per day) are lost daily due to traffic congestion for the road stretches under consideration. This sum will be close to USD 838.44 million on an annual basis. It is a fairly significant expense, particularly when considered in relation to the GDP. Therefore, significant preventative measures need to be implemented in this area. In addition, this is the loss that was sustained as a result of the congestion that occurred along six selected road stretches, when this value is expanded to the whole of the city, the problem becomes far more complicated. As a result, the institutions responsible for formulating policies need to take decisive action to address the issue. The reduction of traffic congestion in Srinagar city can be achieved through enhanced public transportation, congestion pricing, and alternate mobility modalities. Intelligent traffic management, infrastructure development, adaptable work schedules, and urban planning incorporating transit-oriented designs can mitigate congestion.